Forty Years of Family Law: A Retrospective - Parkinson, Patrick (Victoria University of Wellington Law Review, 2015)
This article presents a thematic retrospective of the past 40 years of family law in terms of the international landscape in developed countries. It examines three questions: First, whatever happened to marriage? While once marriage was central to family formation, it is no longer. Indeed, heterosexual couples have never been less interested in the idea of marriage. Secondly, whatever happened to divorce? The nature of divorce has fundamentally changed in the last forty years, largely as a consequence of the recognition that while intimate domestic partnerships may come to an end, parenthood is, for the most part, indissoluble. The ties that bind parents together remain important long after the adult relationship has ended. Thirdly, whatever happened to parenthood? Legal parenthood has become vastly more complicated than in the mid-1970s. One reason for this is the revolution in artificial reproduction techniques. A second reason is that lesbian and gay couples have, in increasing numbers, sought to raise children and demanded recognition of parental rights which are not based on genetic parenthood. These changes have had a profound impact upon modern family law.